Issue 2 - "Update on adverse respiratory effects of indoor air pollution" Part 1): Indoor air pollution and respiratory diseases: A general update and a Portuguese perspective - Cavaleiro Rufo, J (2023)
Objective To quantify the impact of different air pollutants on respiratory health based on robust estimates based on international data and to summarise the evidence of associations between indoor exposure to those pollutants and respiratory morbidity in the Portuguese population. Results Several systematic reviews and meta-analyses (MA) at the world level demonstrate the impact of indoor air quality on respiratory health, with indoor particulate matter and gasses exerting a significant effect on the airways. Volatile organic compounds (VOC) have been related to asthma and lung cancer. However, only meta-analyses on biomass use allowed documentation of long-term respiratory effects. While early publications concerning Portuguese-based populations mainly focused on indoor exposure to environmental tobacco smoke, later studies relocated the attention to relevant exposure environments, such as day care buildings, schools, residences and nursing homes. Looking at the pooled effects from the reviewed studies, high levels of carbon dioxide and particulate matter in Portuguese buildings were significantly associated with asthma and wheezing, with VOC and fungi showing a similar effect in some instances. Conclusions Despite the significant reduction of indoor air pollution effects after the 2008 indoor smoking prohibition in public buildings, studies show that several indoor air parameters are still significantly associated with respiratory health in Portugal. The country shares the worldwide necessity of standardisation of methods and contextual data to increase the reach of epidemiological studies on household air pollution, allowing a weighted evaluation of interventions and policies focused on reducing the associated respiratory morbidity.